Silicone oil-based selective SiOC coating onto hydrophobic rGO-MoS2 composite materials to achieve ultra-stable composite anodes in sodium-ion batteries - Lee, Seunghak; Seok, Eunjeong; Kang, Haeun; Park, Dohyub; Kim, Minjun; Kam, Dayoung; Choi, Minsu; Kim, Hyung-Seok; Choi, Wonchang (한국공업화학회, 2023)
Molybdenum sulfide (MoS2) has a 2-D open framework structure and provide delocalized sodium ion diffusion and intercalation within the MoS2 structure. The structure exhibits a high theoretical capacity due to its wide interlayer spacing (-6.2 & ANGS;). Therefore, MoS2 has recently been used as an anode material in sodium-ion batteries (SIBs). However, it exhibits inferior cycle performance and rate characteristics due to its low electronic conductivity and volume change during continuous operation, which restrict its use as an anode material in SIBs. Herein, a MoS2 surface modified with hydrophobic reduced graphene oxide (rGO-MoS2) was dispersed in silicone oil, which is the starting material for silicon oxycarbide (SiOC), and subsequently used to prepare a MoS2 composite with a SiOC coating-layer surface modified with rGO (rGO-MoS2@SiOC) via single pyrolysis reaction. rGO expands the interlayer spacing of MoS2, improving the electronic conductivity, and the SiOC layer capable of accommodating the volume expansion of MoS2 supports the insufficient buffer layer provided by rGO alone to form a conductive pathway that suppressed any adverse reactions at the electrode and electrolyte interface. The rGO-MoS2@SiOC composite exhibits a high reversible capacity of 532.5 mAh g-1, no capacity fading even after 100 cycles, and superior rate characteristics.& COPY; 2023 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.